Risk and Capital Transfer in Insurance Groups - Gatzert, Nadine; Schmeiser, Hato (Zeitschrift für die gesamte Versicherungswissenschaft, 2008)
The aim of this paper is to analyze the effect of capital and risk transfer instruments (CRTIs) on a financial group's risk situation. In this respect, we extend previous literature by accounting for the conglomerate discount on firm value, which is a reduction in shareholder value due to diversification within the group. In general, CRTIs between parent and subsidiaries have a substantial effect on the diversification of risks, economic capital requirements, and default risk, which we study in detail for different types of CRTIs, including intra-group retrocession and guarantees. One main finding is that diversification effects within the group are much lower when taking into account conglomerate discount effects. We believe this aspect to be an important issue in the ongoing discussion on group solvency regulation and enterprise risk management.
WiSo-Import:2015-03-26:1374
Keywords: Kohäsion